2013
DOI: 10.1007/s13762-013-0355-4
|View full text |Cite
|
Sign up to set email alerts
|

Environmental magnetic studies on surface sediments: a proxy for metal and hydrocarbon contamination

Abstract: Visakhapatnam is one of the major port cities, and it is developed into a hub of many large-and mediumscale industries. Due to growing industrialization and urbanization, coast is vulnerable to both organic and inorganic micro-pollutants. Twenty-five surface sediments were collected along the Visakhapatnam coast for the measurement of texture size, petroleum hydrocarbons, trace metals and environmental magnetic parameters. The percentage of coarser particles was more in the northern region, whereas the percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…The SIRM and % magnetite distributions (Figure 3b,c) were very similar. Higher SIRM values for polluted areas (resulting from vehicle emissions, residential and industrial wastes) have also been reported in previous studies [20,33,34]. The similarity in the mean χ FD % values for samples in the R and NR areas ( Table 1) implies that the samples contained both SP and non-SP grains [2,28,29].…”
Section: Discussionsupporting
confidence: 73%
“…The SIRM and % magnetite distributions (Figure 3b,c) were very similar. Higher SIRM values for polluted areas (resulting from vehicle emissions, residential and industrial wastes) have also been reported in previous studies [20,33,34]. The similarity in the mean χ FD % values for samples in the R and NR areas ( Table 1) implies that the samples contained both SP and non-SP grains [2,28,29].…”
Section: Discussionsupporting
confidence: 73%
“…PHC concentrations obtained here are compared with previously reported values (Table 3). In the context of India, most previous studies have focused on coastal environments, such as the Visakhapatnam coast (Venkatachalapathy et al 2013), Tamilnadu coast , Chennai coast (Table 3). As classified by US National Academy of Sciences (NAS 1975), >70 ppm is considered as indication of pollution.…”
Section: Resultsmentioning
confidence: 99%
“…To date, there has been limited investigation on the extent of PHC in Indian lagoon ecosystems. Venkatachalapathy et al (2013), Lyla et al (2012) and have studied the distribution of PHC withinIndia. A total of 52 rivers and rivulets drain into the lagoon, out of which the northeast rivers contribute about 80% of the annual freshwater load.…”
mentioning
confidence: 99%